Research on forensics of privacy violations in cloud environment - Weifeng LI; Weizhong QIANG; Weiming LI; Deqing ZOU (网络与信息安全学报)
Cloud computing is the mainstream information system technology,however,privacy protection of user and privacy violation tracking and forensics in the cloud computing environment have always been a challenge.The current mainstream cloud computing forensics system and standard are not mature and complete,and are far from the target of computer forensics.With the focus on privacy violation and forensics in the cloud environment,status and challenges of cloud forensics and cloud privacy violation were reported firstly.Then,the research content and technical route of privacy forensics in the cloud environments were analyzed.Finally,a specific privacy violation forensics system for cloud environments was presented.